V.ii.1. Dr. Evory Kennedy ephemera, - Kennedy, Evory, 1806-1886. (1836)
Contains a purchase of Blessington lands by Dr. Evory Kennedy for his sisters, Eacy Kennedy and Mary Collins, and an excise permit. Also contains extracts from "Reminiscences of my Irish journey in 1849" by Thomas Carlyle, in which Dr. Kennedy is mentioned.